A new approach for impedance matching rotman lens using defected ground structure - Mohammed K. Al-Obaidi; Ezri Mohd; Noorsaliza Abdullah; Samsul Haimi Dahlan (Bulletin of Electrical Engineering and Informatics, 2020)
Many recent radar applications and smart antenna are based on the electronically steerable beam in order to increase the performance of targeting the desired scan angle with the high performance of gain and directivity. Scanning angle with ±26o based on Microstrip Rotman lens and design frequency 2.45 GHz is presented in this study. Five beam ports provide five output beams directed the beams in five different scanning angles in the azimuth plane is provided. The traditional matching method by tapering the transmission line in order to guarantee a smooth energy transition from the 50 Ω input ports is replaced by Defected Ground Structure to achieve an acceptable return loss with a linear progressive phase for each beam port. The new approach is providing increasing in the scan angle. Besides, the size miniaturization is achieved by removing the tapering length and reduces the total size of the lens length by 23.67 mm. The proposed model is implemented using Computer Simulation Technology (CST) using the FR-4 substrate and the measurements lead to a good validation.